Сын тұрғысы арқылы оқытудың ерекшелігі - Қасаболат, А.Ж. (My University, 2016)
Examine the features of education in the field of training in improving the quality of primary education through critical thinking and enhances the relevance of the topic. Previously, the main role of the teacher in the learning process, now is the time, providing the student's activity. Lesson the teacher, not the student action is evaluated. The purpose of the article the research skills of students in the lesson and zdeno, forming what technology definitions for the purpose of enhancing the interest to the subject. Technology of critical thinking in education through certain ideas, assuming that's why his research, the ability to put them against light septic thoughts, in comparison, against those ideas, perspectives, proportions of study to be taught and be confident in them. The Director explained that in the case of themes, the teacher sums up the knowledge, not the controller, evaluator, cognitive activities, collective creative Affairs, organized by the kernel.
Keywords: Student; teacher; critical thinking; action; creative personality; intelligence